Estudo clínico e epidemiológico das apresentações iniciais de pacientes com transtorno afetivo bipolar–tipo I e II - Chaves, Moysés de Paula Rodrigues (2013)
There are several studies on the differential diagnosis of Bipolar Disorder (BD), however, further investigation with an emphasis on clinical phenotypes that inaugurate the disease is needed. The aims of this study are to identify the psychiatric disorders most frequently diagnosed before the definitive diagnosis of BD, the time until the correct diagnosis and compare BD I and II for the variables studied. We studied 259 patients with current diagnosis of BD according to the DSM- IV-TR, evaluated by the same psychiatrist. Early psychiatric signs and symptoms were identified through an interview with the patient and family members and were considered suggestive of an initial diagnosis that was coded according to the same diagnostic criteria. The authors analyzed data on patients' age at prodromes suggestive of initial psychiatric diagnosis and time delay to the actual diagnosis of BD. Comparisons were made between sex, schooling and type of BD. The mean age of patients was 41.6 years, with a predominance of adults (19-60 years), women (67.6%), as well as type II BD (68.3%). Patients were on average 24.6 years of age at initial diagnosis, 41.6 years in the diagnosis of BD and the mean time delay between these was 16.9 years. The most common initial diagnoses were depressive disorders (41.3%), anxiety (12.7%), ADHD (8.1%), disorders related to substance abuse (7.7%), somatoform disorders (6 9%), and psychosis (5.4%). BD can be considered a “great imitator” in modern psychiatry, since initial phenotypes can mimic other disorders. BD diagnosis is very delayed in Brazil.